Women characters in baseball literature a critical study - Sullivan, Kathleen (McFarland & Co., 2005)
"This is the first comprehensive evaluation of the women characters of baseball literature, including women's crucial roles on and off the field of play. Applying several feminist theories and examining the works in the context of both myth and psychology, the author discusses baseball fiction written by both men and women"--Provided by publisher.